Start your own restaurant and more : pizzeria, coffeehouse, deli, bakery, catering business / Jacquelyn Lynn ; Entrepreneur Media, Inc. - Lynn, Jacquelyn
Provides information for starting a restaurant business, covering evaluating competition, set-up, staffing, permits, marketing, inventory, location, and more